Rare resected eight cases of duodenal adenocarcinomas. (September 2021) - Nanashima, Atsushi; Tanoue, Yukinori; Imamura, Naoya; Hiyoshi, Masahide; Yano, Koichi; Hamada, Takeomi; Nishida, Takahiro; Kai, Kengo; Suzuki, Yasuto; Sato, Yuichiro; Nakashima, Koji; Hosokawa, Ayumu; et al.
Abstract: Introduction: Duodenal adenocarcinoma is a rare malignancy; recently, it has been found to be accompanied by operative indications. Methods: Nine consecutive rare cases were diagnosed with duodenal carcinoma (DC), in which clinicopathological characteristics were retrospectively examined. Age was ranged over middle-aged males and females. No clinical onset with severe symptoms was observed, and the specific treatment for accompanied diseases or habits was not found. Outcomes: One case of two T1 stage DCs that underwent pancreas-sparing duodenectomy. Stage II DC was diagnosed in three cases, and stage III DC was diagnosed in four cases. Pancreaticoduodenectomy (PD) mainly occurred in seven patients, and duodenectomy was limited in two patients. All operations were safely performed, and the postoperative course showed no severe morbidity. Histological findings showed R0 resection in eight cases and R1 at the retroperitoneal dissecting part in one case. Five patients with advanced-stage DC underwent adjuvant chemotherapy; however, four patients showed tumor recurrence within 12 months. With additional strong chemotherapy, eight patients survived up to 84 months, and one died of liver metastasis at 43 months after surgery. Three representative cases of mucosal invasion with widespread pancreas-sparing duodenectomy and advanced-stage DC cases undergoing duodenectomy or PD are shown. Conclusion: In the field of upper digestive tract surgery, duodenal adenocarcinoma and various applications of surgery or adjuvant chemotherapy for long-term survival are important. Highlights: Duodenal cancer used to be rare disease and, however, we have increasingly experienced surgical intervention for duodenal cancers because it might be due to development of duodenal endoscopic examination. For early cancers, duodenal resection preserved surrounding organs such as a pancreas can be indicated, otherwise pancreaticoduodenectomy is necessary for advanced stage duodenal cancer located up to 3rd portion of duodenum. Patient prognosis can be expected by the novel adjuvant chemotherapy after curative duodenectomy.